2016
DOI: 10.22456/1679-9216.81097
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin and Immunoglobulin G Concentration in Bovine Milk from Cows with Subclinical Mastitis during the Late Lactation Period

Abstract: Background: Lactoferrin and immunoglobulin G in milk have an important role in udder resistance to infection in the involution period. Both proteins express antimicrobial activity- lactoferrin by the binding and sequestration of iron ion; and immunoglobulin G by complement activation, bacterial opsonization and agglutination. Many factors affect lactoferrin and immunoglobulin G concentrations in bovine milk, such as the stage of lactation, milk production, and intramammary infections. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Concerning test characteristics for goats and cows, two studies carried out a competitive ELISA by using a lactoferrin antiserum from rabbit, and goat lactoferrin was isolated and purified (Chen and Mao 2004 ; Chen et al 2004 ). In other studies, cow LF was quantified by a commercial sandwich LF ELISA kit (Bethyl Laboratories, Montgomery, TX) (Cheng et al 2008 ; Sobczuk-Szul et al 2014 ; Galfi et al 2016a , 2016b ). For water buffalo, a specific ELISA kit was produced for the study (Özenç et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning test characteristics for goats and cows, two studies carried out a competitive ELISA by using a lactoferrin antiserum from rabbit, and goat lactoferrin was isolated and purified (Chen and Mao 2004 ; Chen et al 2004 ). In other studies, cow LF was quantified by a commercial sandwich LF ELISA kit (Bethyl Laboratories, Montgomery, TX) (Cheng et al 2008 ; Sobczuk-Szul et al 2014 ; Galfi et al 2016a , 2016b ). For water buffalo, a specific ELISA kit was produced for the study (Özenç et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of LF in milk is due to secretion by epithelial cells and degranulation of PMNs during inflammation (Lash et al 1983). Even though LF is not an APP, it increases remarkably during the inflammatory response due to its production by mammary epithelial cells (Galfi Galfi et al 2016aGalfi et al , 2016b. For water buffalo, a specific ELISA kit was produced for the study (Özenç et al 2019).…”
Section: Lactoferrin (Lf)mentioning
confidence: 99%
“…Increases in the concentration of bovine lactoferrin and bovine serum albumin in milk have been used as indicators of bovine mammary involution previously [ 29 , 33 , 34 , 36 ]. Besides being an indicator of mammary involution, bovine lactoferrin plays an immunologically important role during mammary involution, by binding available iron and making it unavailable for iron-dependent bacteria to grow [ 37 , 38 ]. It has been reported that lactoferrin presents a robust defense against IMI [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being an indicator of mammary involution, bovine lactoferrin plays an immunologically important role during mammary involution, by binding available iron and making it unavailable for iron-dependent bacteria to grow [ 37 , 38 ]. It has been reported that lactoferrin presents a robust defense against IMI [ 36 , 37 , 38 ]. One week after drying off, the concentration of lactoferrin was higher in cows that were treated with casein hydrolysate compared with the controls and all but one other treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A positive effect of OAD is a significant increase in the content of valuable bioactive molecules, such as lactoferrin (LF), and other immune-related proteins in milk, such as acute phase proteins and RNases (Farr et al, 2002;Stelwagen et al, 2011). LF is produced in bovine milk as part of a wide range of bioactive proteins and peptides, which have roles in immunity and immunoregulation functions (Galfi et al, 2016). LF has been found to have antibacterial activity for bacteria with high iron requirements like Escherichia coli and Staphylococcus aureus, coagulase negative Staphylococcus sp.…”
mentioning
confidence: 99%